AB0283 IDENTIFICATION OF NEW AUTOANTIBODIES FOR RHEUMATOID ARTHRITIS USING HUMAN PROTEOME MICROARRAYS. (June 2019) - Lin, LI; Tao, Jinhui; Zhang, Hong-Liang; Tang, Yu-Jie; Xin-Ya, LI; Lu, Qun-Qun; Wang, Ya-Ling; Zhu, Zi-Wen
Abstract : Background: Rheumatoid arthritis is an autoimmune disease characterized by symmetrical small arthritis. Anti-cyclic citrullinated peptide antibodies and rheumatoid factor are commonly used to diagnose RA [1] . However, the early diagnosis of RA is sometimes difficult, due to the heterogeneity and negative anti-CCP antibody or RF in some patients. Therefore, it is urgent to find autoantibodies with high sensitivity and specificity as diagnostic markers for RA. Objectives: To screen autoantibodies of RA with high sensitivity and specificity using human proteome microarrays [2] . Methods: Firstly, a case-control method was used to analyze the serum antibodies of RA patients using human proteome microarray which composed of 20, 000 proteins, and identified RA-related antibodies. Then, expanded the sample size and analyzed the expression of these candidates between RA patients and healthy controls. Results: The serum of five RA patients and five healthy controls were selected to detect the RA-related autoantibodies by microarray, and 25 candidates were screened. Then the IgG and IgM RA-focused microarrays composed of the 25 proteins were screened with additional cohorts of 72 RA patients and 106 healthy controls. The results of IgG protein microarray showed: (1) Expression of these 25 autoantibodies in RA patients was significantly higher than those in healthy controls ( P <0.05). (2) There was nodifferentially expressed protein between anti-CCP antibody and RF-negative RA patients (n=18) and anti-CCP antibody and/or RF-positive RA patients (n=54) ( P >0.05). (3) ROC analysis showed that the combination of anti-RBPJ, anti-SH3BGR and anti-PAFAH1B3 autoantibody can be highly RA-specific biomarkers, with 66.7% sensitivity and 74.2% specificity, and the area under the curve is 0.734; meanwhile the sensitivity and specificity of the anti-CCP antibody and RF-negative RA patients diagnosis were 77.8% and 65.6%, and the area under the curve was 0.720. The results of IgM protein microarray showed: (1) Only 10 out of the 25 candidates' expression was significantly higher in RA patients than healthy controls ( P <0.05). (2) Compared with anti-CCP antibody and/or RF-positive patients, the expression of anti-PAFAH1B3, anti-RBPJ, anti-SH3BGR, anti-UBA5, anti-ANP32A, anti-PAGE2, anti-SHFM1 and anti-PDE1B was found significantly higher in anti-CCP and RF-negative patients ( P <0.05). (3) ROC analysis showed that anti-PAFAH1B3 antibody was identified to diagnose RA with 76.2% sensitivity and 72.9% specificity, and the area under the curve was 0.768; however, there were no significance for the diagnosis of anti-CCP antibody and RF-negative RA patients ( P =0.160). Conclusion: The combination of IgG-type antibodies anti-RBPJ, anti-SH3BGR and anti-PAFAH1B3, the IgM-type antibody anti-PAFAH1B3 as well, has high sensitivity and specificity for the diagnosis of RA; especially the IgG-type autoantibody combination has great value for the diagnosis of anti-CCP and RF-negative RA patients. References: [1] Silveira IG, et al. Anti-CCP antibodies have more diagnostic impact than rheumatoid factor (RF) in a population tested for RF. Clinical Rheumatology, 2007. 26(11): p.1883-1889. [2] Song Q, et al. Novel Autoimmune Hepatitis-Specific Autoantigens Identified Using Protein Microarray Technology. Journal of Proteome Research, 2010. 9(1): p.30-39. Acknowledgement: This work was supported by grants from the National Natural Science Foundation of China (81771774) and the Anhui Provincial Natural Science Foundation (1708085MH191) Disclosure of Interests: None declared